Elucidating influence of the existence formation of anchored cobalt phthalocyanine on electrocatalytic CO2-to-CO conversion. (June 2021) - Gong, Shanhe; Wang, Wenbo; Xiao, Xinxin; Liu, Jun; Wu, Chundu; Lv, Xiaomeng
Abstract: Heterogeneous molecular catalysts with inexpensive transition-metal centers have attracted much attention, due to their excellent electrocatalytic performance on electrocatalytic carbon dioxide reduction reaction (CO2 RR). Among them, metal phthalocyanine (MePc) has aroused great interest. However, the complex existence formation (crystals or evenly dispersion) in the hybrid catalyst, e.g. cobalt (II) phthalocyanine (CoPc), determining the final electrocatalytic CO2 RR performance still remains debate. To further elucidate the influence of the existence formation of CoPc on electrocatalytic performance of CO2 -to-CO conversion, we synthesized ultra-thin nitrogen-doped hollow carbon spheres (N-doped HCS) with a high surface area of 653.3 m 2 g −1 as the support to anchor a series of different existence formation of CoPc. The existence formation of CoPc in the hybrid catalyst is closely related with the content of Co atom, the latter of which is the key factor of the CO2 RR performance. We summarized the nonlinear relationship between the partial CO current density ( j CO ) and the content of Co atom at −0.82 V vs. RHE, and the equation of Faraday efficiency of CO ( FE CO ) vs. the content of Co atom at −0.82 V vs. RHE, which proves the fact that the coexistence of crystals and evenly dispersed CoPc or evenly dispersed and low loading of CoPc both could reach the satisfying results ( j CO > 14 mA cm −2, FE CO > 91%, at −0.82 V vs. RHE) under the content of Co atom from 1.26 wt% to 0.14 wt%. The optimal catalyst (Co, 0.49 wt%) achieved a near-unity Faradaic efficiency of 96%, which is close to 4 times that of the unsupported CoPc ( FE CO =24.54%), and an outstanding current density of 20.47 mA cm −2 towards CO, which is c.a. 60 times higher than that of the unsupported CoPc (0.34 mA cm −2 ) at −0.82 V vs. RHE. This work could potentially inspire the rational design of heterogeneous molecular catalysts and promote its application in the energy conversion and storage field. Graphical Abstract: The nitrogen-doped porous hollow carbon spheres anchor a series of cobalt phthalocyanine for electrocatalytic carbon dioxide reduction. ga1 Highlights: Different amount of Cobalt (II) phthalocyanine (CoPc) is immobilized on N-doped HCS as electrocatalysts. Their electrochemical CO2 RR properties were found to be closely related with the existence formation of CoPc. The nonlinear relationship of existence formation of CoPc and electrocatalytic performance is discussed and elucidated. Optimized catalyst is enumerated with excellent value of multiparameters. The mechanism of electroreduction CO2 -to-CO conversion is deduced for better understanding.